Applicants’ reactions to technology-mediated interview: a hybrid thematic analysis - Alias, Alizi; Mohd. Taib, Maisarah (2014)
This research investigated applicants’ reactions to technology-mediated interview using qualitative method. Data were obtained from 46 job applicants applying for a job as research assistant and were analysed using hybrid thematic analysis. Hybrid thematic analysis enabled identification of overarching themes that captured the phenomenon of applicants’ reactions as described by the job applicants. The analysis generated eight main categories: (1) predictive validity perceptions, (2) perceived job-relatedness, (3) perceived process fairness, (4) perceptions of organisational attractiveness, (5) perceptions of organisation technological sophistication/effectiveness, (6) intentions toward the organisation, (7) perceived effective two-way communication, and (8) self-perception outcomes. Findings also suggest that applicants’ reactions may occur before, during and even after the employment interview session. Similar and different findings compared to past research were also discussed.